1999
DOI: 10.2307/1183067
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Active-Student Learning Using the World Wide Web in Economics Courses

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The potential advantages claimed of using Internet tools over traditional teaching methods in economics education have been discussed widely in the literature (Sosin, 1997;Agarwal & Day, 1998;Simkins, 1999;Lage et al, 2000). These advantages include easy and rapid access to knowledge and information, fast and asynchronous communication, cost-saving, learner-centred content, learner control and use of the messages, and reach to a diversity of student cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential advantages claimed of using Internet tools over traditional teaching methods in economics education have been discussed widely in the literature (Sosin, 1997;Agarwal & Day, 1998;Simkins, 1999;Lage et al, 2000). These advantages include easy and rapid access to knowledge and information, fast and asynchronous communication, cost-saving, learner-centred content, learner control and use of the messages, and reach to a diversity of student cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Such examples in economics education include Lage et al (2000), Parks (1999), Vachris (1999), Simkins (1999) and Agarwal and Day (1998). 1 The unique attributes of Internet tools may benefit students' learning experience by offering a new medium of interaction that complements classroom instruction, giving additional tools to support students' studies, facilitating idea generation and evaluation and record keeping, and yielding positive externalities for future employment, further study and/or research, and engagement in lifelong learning (see Simkins, 1999;Gal-Ezer & Lupo, 2002;Parkinson & Hudson, 2002). However, though the use of Internet tools in economic pedagogy is growing, there is no firm evidence to prove that Internet tools can make a substantial difference in improving teaching and enhancing learning.…”
Section: Introductionmentioning
confidence: 99%
“…Greenlaw (1999) reviewed the use of these sorts of tools at length. Simkins (1999) described classes using a simulated Federal Reserve meeting where the meet-…”
Section: Discussionmentioning
confidence: 99%
“…Research studies of ICT use in economics courses have shown that ICT empowers students and enables them access to the discipline (Smith & Smith, 1989;Hallberg, 1996;Katz, 1999;Simkins, 1999). WinEcon is chosen for this study because of its comprehensiveness as a tutorial-based hypermedia, and its exibility and scope of incorporating other ICT tools.…”
Section: Winecon and The A-level Economics Coursementioning
confidence: 99%